Postcardiotomy Venoarterial Extracorporeal Membrane Oxygenation With and Without Intra-Aortic Balloon Pump - Björnsdóttir, Björk; Biancari, Fausto; Dalén, Magnus; Dell'Aquila, Angelo M; Jónsson, Kristján; Fiore, Antonio; Mariscalco, Giovanni; El-Dean, Zein; Gatti, Giuseppe; Zipfel, Svante; Perrotti, Andrea; Bounader, Karl; et al. (Journal of cardiothoracic and vascular anesthesia, 2022)
OBJECTIVES: To compare the outcomes of patients with postcardiotomy shock treated with venoarterial extracorporeal membrane oxygenation (VA-ECMO) only compared with VA-ECMO and intra-aortic balloon pump (IABP). DESIGN: A retrospective multicenter registry study. SETTING: At 19 cardiac surgery units. PARTICIPANTS: A total of 615 adult patients who required VA-ECMO from 2010 to 2018. The patients were divided into 2 groups depending on whether they received VA-ECMO only (ECMO only group) or VA-ECMO plus IABP (ECMO-IABP group). MEASUREMENTS AND MAIN RESULTS: The overall series mean age was 63 ± 13 years, and 33% were female. The ECMO-only group included 499 patients, and 116 patients were in the ECMO-IABP group. Urgent and/or emergent procedures were more common in the ECMO-only group. Central cannulation was performed in 47% (n = 54) in the ECMO-IABP group compared to 27% (n = 132) in the ECMO-only group. In the ECMO-IABP group, 58% (n = 67) were successfully weaned from ECMO, compared to 46% (n = 231) in the ECMO-only group (p = 0.026). However, in-hospital mortality was 63% in the ECMO-IABP group compared to 65% in the ECMO-only group (p = 0.66). Among 114 propensity score-matched pairs, ECMO-IABP group had comparable weaning rates (57% v 53%, p = 0.51) and in-hospital mortality (64% v 58%, p = 0.78). CONCLUSIONS: This multicenter study showed that adjunctive IABP did not translate into better outcomes in patients treated with VA-ECMO for postcardiotomy shock.
Keywords: senioři; venoarterial extracorporeal membrane oxygenation; intraaortální balónková pumpa; Male; Retrospective Studies; mimotělní membránová oxygenace; Intra-Aortic Balloon Pumping; Middle Aged; mužské pohlaví; Cardiac Surgical Procedures; Adult; Shock; Shock, Cardiogenic; ženské pohlaví; retrospektivní studie; kardiochirurgické výkony; Extracorporeal Membrane Oxygenation; Humans; šok; intra-aortic balloon pump; lidé středního věku; Heart-Assist Devices; postcardiotomy; kardiogenní šok; dospělí; cardiogenic shock; Female; Aged; lidé; podpůrné srdeční systémy